Construction of Personal Branding of Ceu Popong as a Sundanese Woman Politician through Television Media - Setiawan, Mursyid (Jurnal Civicus, 2023)
The formation of personal branding has become one of the most important political communication strategies for shaping the image of a politician. One of them is Popong Otje Djundjunan, often known as Ceu Popong. One of the ways to establish Ceu Popong's personal branding as a female politician is through television media, namely the Ngawangkong Sareng Ceu Popong program on INews Bandung television station. This study aims to analyze the construction of Ceu Popong's personal branding as a Sundanese female politician through television media. The analysis was carried out based on eight aspects of personal branding identified by Peter Montoya and Tim Vandehey (2002). A qualitative approach and case study method are used in this research. Data were collected using interviews, observation, and documentation studies. The results showed that Ceu Popong's personal branding as a female politician was formed through one of the INews Bandung television programs, namely Ngawangkong Sareng Ceu Popong. Eight aspects of personal branding, starting with specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill, have been formed in Ceu Popong when presenting the television program. The formation of personal branding through television media has constructed the Ceu Popong brand as a female politician who is attached to Sundanese cultural values.